Article Review: The Role of Cyrtorhinus lividipennis in Rice Planthoponus Control and Food Security - Maulin Eka Cahyani; Rafa Aida Ainur Risna; Aura Helga Primadani; Sultan Nugraha; Loekas Soesanto (Jurnal Biologi Tropis, 2026)
Rice (Oryza sativa L.) is the primary food source for the majority of the world’s population, particularly in Asia. Leafhoppers are among the primary organisms that damage farmers’ crops, especially rice. Improper control measures, particularly the use of insecticides, can lead to negative impacts such as pest resistance and resurgence; furthermore, the use of insecticides can reduce natural enemy populations. The use of natural predators such as Cyrtorhinus lividipennis serves as an alternative in biological control. This article aims to examine the role of C. lividipennis in controlling brown planthopper populations in rice crops and its impact on food security. The method used was a literature review analyzing various research findings related to brown planthopper population dynamics, predator density, predation rates, and their impact on rice productivity. The results of the study indicate that the presence of C. lividipennis can significantly suppress brown planthopper populations through predation, with predation rates of 50–80%. Predator density is negatively correlated with brown planthopper populations. The impact of this control is also evident in reduced crop damage and increased rice growth and productivity. Thus, C. lividipennis has the potential to serve as a biological control agent to support food security.